Association of dopamine receptor D2 -141C insertion/deletion and dopamine beta-hydroxylase 19 bp insertion/deletion polymorphisms with schizophrenia: A case-control study in the eastern Algerian population - Boukhenaf Yasmina; Sariyah Ayachi Ouarda; Achou Rayene; Iness Bernou Amina; Zohra Madoui Fatima; Sifi Karima; Larbi Rezgoun Mohamed (Archives of Biological Sciences)
Numerous studies emphasize genetic contributions to schizophrenia, particularly focusing on genes coding for proteins in the dopaminergic pathway, which are extensively studied for their involvement in the disorder’s pathophysiology. This investigation aimed to examine the potential association between the dopamine receptor D2 (DRD2) -141C insertion/ deletion (rs1799732) and the dopamine beta-hydroxylase (DBH) 19 bp insertion/deletion (rs72393728) polymorphisms with schizophrenia in an eastern Algerian population. A case-control study was conducted, involving 145 patients and 146 healthy controls. DNA samples were extracted from peripheral blood cells using the salting out technique. Genotyping for the DRD2 rs1799732 polymorphism was performed using the PCR-RFLP method, while the DBH rs72393728 polymorphism was analyzed using the PCR method. The results revealed a significant association between the DRD2 rs1799732 polymorphism and schizophrenia, evidenced by significant differences in genotypic and allelic distributions between patients and controls (P=0.001 and P=0.001, respectively). However, no statistical differences were found for the DBH rs72393728 polymorphism between patients and controls for genotype (P=0.46) or allele frequencies (P=0.73). This study supports an association between DRD2 rs1799732 polymorphism and schizophrenia in this population while finding no such association with DBH rs72393728 polymorphism. However, there may be a potential interaction between both polymorphisms.